PERAN LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MEMBERDAYAKAN PEREMPUAN PAPUA (Studi Kasus Bank Wakaf Mikro Honai Sejahtera Papua) - Fachrudin Fiqri Affandy; Ira Eka Pratiwi; Shimah Fauziyah Yeubun (PSGA LP2M IAIN Pontianak, 2022)
Every woman has a role in life. The stigma of women who are limited to “mattress, kitchen, and well” slowly needs to be changed. In the economic context, women become a partner for their husbands in meeting the needs of life. There needs to be a sustainable way to empower women, including Papuan women. Women need to be allowed to be empowered and have an economic impact on their families. This paper tries to examine the role of the Islamic Microfinance Institution (LKMS) in this case is the Honai Sejahtera Papua Micro Waqf Bank in carrying out community empowerment programs around pesantren towards women as the objects. The efforts taken include assisting, providing marketing facilities, and providing working capital loans. The presence of the Honai Sejahtera Papua Micro Waqf Bank certainly can have a positive impact on the community, especially on Papuan women. The desire to change lives through economic activities is the main goal of Papuan women to take part in the program.